An inflated Multivariate Integer Count Hurdle model: An application to bid and ask quote dynamics - Katarzyna Bien; Ingmar Nolte; Winfried Pohlmeier (University of Konstanz, Center of Finance and Econometrics (CoFE), 2007)
In this paper we develop a model for the conditional inflated multivariate density of integer count variables with domain Zn. Our modelling framework is based on a copula approach and can be used for a broad set of applications where the primary characteristics of the data are: (i) discrete domain, (ii) the tendency to cluster at certain outcome values and (iii) contemporaneous dependence. These kind of properties can be found for high or ultra-high frequent data describing the trading process on financial markets. We present a straightforward method of sampling from such an inflated multivariate density through the application of an Independence Metropolis-Hastings sampling algorithm. We demonstrate the power of our approach by modelling the conditional bivariate density of bid and ask quote changes in a high frequency setup. We show how to derive the implied conditional discrete density of the bid-ask spread, taking quote clusterings (at multiples of 5 ticks) into account.
urn:nbn:de:bsz:352-opus-32415
Keywords: G10; F30; C30; 330; Multivariate Discrete Distributions; Conditional Inflation; Copula Functions; Truncations; Metropolized-Independence Sampler; Multivariate Analyse; Qualitatives Verfahren; Zeitreihenanalyse; Statistische Verteilung; Bid-Ask Spread; Theorie